IMPLEMENTASI LATIHAN PRENATAL YOGA TERHADAP PENURUNAN TINGKAT KECEMASAN PADA IBU HAMIL TRIMESTER III DI RUMAH SAKIT UMUM DAERAH LABUANG BAJI MAKASSAR - Kasim, Erna; Nurfadillah; Limbong, Magdalena; Ahmad, Ekayanti Hafidah (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2025)
During the pregnancy period, pregnant women experience physiological and psychological changes that cause the mother. Pregnancy becomes uncomfortable, so your emotions tend to change. As gestational age increases, pregnant women generally begin to feel anxiety, especially in the third trimester. Descriptive case study approach carried out on 2 respondents with the The inclusion criteria are primigravida mothers, third trimester pregnant women whose pregnancy lasts 28-37 weeks, never taking part in prenatal care, women who have not had other treatments, being responsive and following through until delivery and erkslursion criteria, namely pregnant women who experience complications during pregnancy. such as hypertension, bleeding, and prerclampsia, pregnant women who have physical disabilities (unable to perform yoga movements) . The results of the survey research carried out the implementation of prenatal yoga on respondents who experienced severe anxiety. serdang. There is an influence of the prenatal yoga techniques serberlurm and sersurdah on fertility. So it can be concluded that there is a difference or difference in the level of intelligence among pregnant women in the Anter Natal Carer (ANC) Hospital Laburang Baji Makassar in 2024. After conducting a case study, it was concluded that the application of prenatal yoga can reduce the level of anxiety in third trimester pregnant women who are about to face childbirth